More grain legumes for Africa - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1987)
The International Crops Research Institute for the Semi-Arid Tropics (ICRISAT), India, will increase its presence in Eastern and Central Africa for grain legume promotion, reports the institute's bulletin. A consultative group meeting on Grain...